PENERAPAN PEMBELAJARAN DENGAN PENDEKATAN BERMAIN UNTUK MENINGKATKAN HASIL BELAJAR LARI 60 METER PADA SISWA KELAS IV UPT SPF SDI KAMPUS IKIP KOTA MAKSSAR - Nursamsi Nursamsi; Rahmad Risan (Jurusan Pendidikan Teknik Elektro, 2024)
Students taking PJOK lessons, especially in athletics learning in the 60 meter running sport, have not yet reached the maximum level of completion of the Minimum Completion Criteria (KKM). This research aims to increase the value of learning outcomes in the 60 meter running material for elementary school students by implementing learning with a play approach for class IV students at UPT SPF SDI IKIP CAMPUS. This research uses the classroom action research (PTK) method with data collection techniques in the form of direct observation. The subjects of this research were all fourth grade elementary school students, with a total of 17 participants. This research activity consists of planning, implementation, observation and reflection. Data is collected through tests and measurements, observation, and documentation. From the results of the analysis, it was found that there was an increase from the initial conditions to cycle I and cycle II. The data obtained showed an increase in the ability to run 60 meters and learning outcomes in initial conditions (35.2%), cycle I (64,7%), and cycle II (88.2%), so that the increase from initial conditions to cycle II was ( 53%).